Preparation and Structural Characterization of Rice Bran Protein Hydrolysates and Their Binary Nanoparticles - WANG Na, BU Huifang, SUN Yuzhuo, SHAO Xulong, BAI Xilei, XIAO Zhigang, ZHANG Xiuling (Shipin Kexue, 2025)
To improve the solubility, stability and bioactivity of rice bran protein (RBP) and its hydrolysates and to enhance their utilization as biological carriers, this study prepared binary nanoparticles composed of rice bran protein hydrolysates and gum arabic (GA) by taking advantage of the interaction between proteins and polysaccharides. Trypsin hydrolysate (R-t) and alkaline protease hydrolysate (R-a) of RBP were prepared and their physicochemical and structural properties were determined. Subsequently, each hydrolysate was combined with GA to prepare binary nanoparticles, which were characterized using intermolecular interaction analysis, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. The results showed that the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity of R-t and R-a were (72.82 ± 1.95)% and (66.83 ± 2.34)%, respectively, which were significantly higher than that of RBP. R-t-G nanoparticles with good stability were obtained at pH 1.4, R-t/GA ratio of 1:1 (m/m), and total polymer concentration of 4 mg/mL. R-a-G nanoparticles with good stability were obtained at pH 1.4, R-a/GA ratio of 1:2.5 (m/m), and total polymer concentration of 4 mg/mL. Electrostatic interaction played a significant role in the binding of R-t and R-a to GA, thereby stabilizing the structure of nanoparticles, and R-t-G exhibited a more stable system compared with R-a-G, with superior dispersion, thermal stability and a stronger crystal structure.